Digital Leadership and Employee Creativity in Work Environments: Mediation of Psychological Safety and Knowledge Sharing Behavior - Haris Budiyono; Rianti Setyawasih (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This research is grounded in the increasing adoption of hybrid work models following digital transformation, which has created new challenges in maintaining employee creativity, collaboration, and innovation. This study examines the influence of digital leadership on employee creativity in hybrid work environments, with psychological safety and knowledge-sharing behavior as sequential mediators. The study employed a quantitative explanatory design using a cross-sectional survey of 200 employees working in hybrid organizations in West Java, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital leadership has a significant positive effect on employee creativity, psychological safety, and knowledge-sharing behavior. Psychological safety significantly enhances knowledge-sharing behavior, which in turn strongly predicts employee creativity. Furthermore, the sequential mediation analysis confirms that psychological safety and knowledge-sharing behavior jointly mediate the relationship between digital leadership and employee creativity. These findings suggest that digital leadership fosters creativity not only directly but also through psychological and behavioral mechanisms that support collaborative learning. In conclusion, employee creativity in hybrid environments is largely shaped by an integrated process involving leadership, psychological safety, and knowledge exchange, highlighting the importance of supportive digital leadership practices in modern organizations.